La pigmentacion de Fusarium verticillioides (SACC.) como factor de virulencia en plantulas de maiz - Solano Baez, A.R.=700 1 De Leon Garcia De Alba, C.; Valdovinos Ponce, G.; Silva Rojas, H.V.; Soto Rojas, L.
(Es, En)
Ilus., 41 ref.
Keywords: ZEA MAYS; PLANTULAS; FUSARIUM; PIGMENTACION; MICELIO; COSTA RICA; MICELIO MORADO; MICELIO BLANCO; SEMILLA SINTOMATICA; SEMILLA ASINTOMATICA; AGRONOMIA MESOAMERICANA